Impact of Digital Technologies on Enhancing Supplier Collaboration and Performance in Sweden - Hugo, Adrian (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The aim of the study was to examine the Impact of Digital Technologies on Enhancing Supplier Collaboration and Performance in Sweden. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study that impact of digital technologies on enhancing supplier collaboration and performance in Sweden has been transformative, driving significant improvements in efficiency, transparency, and strategic alignment. The adoption of digital tools such as cloud-based platforms, blockchain, and advanced data analytics has enabled Swedish businesses to foster stronger, more collaborative relationships with their suppliers. Digital technologies have streamlined communication and information sharing, allowing for real-time data exchange and more effective coordination across the supply chain. This enhanced transparency has reduced the risk of errors, improved order accuracy, and facilitated more agile and responsive supply chain operations. Consequently, businesses have been able to reduce lead times, optimize inventory levels, and enhance overall supply chain resilience. Unique Contribution to Theory, Practice and Policy: Resource Dependence Theory, Transaction Cost Economics & Social Exchange Theory may be used to anchor future studies on Impact of Digital Technologies on Enhancing Supplier Collaboration and Performance in Sweden. Organizations should prioritize investment in robust digital platforms and tools that facilitate real-time communication, transparency, and data-driven decision-making across supply chains. This includes adopting cloud-based collaboration tools, implementing AI-driven analytics for predictive insights, and integrating IoT for enhanced visibility. Implementing structured SRM strategies that leverage digital technologies can improve supplier engagement, trust, and performance. This involves establishing clear communication channels, setting performance benchmarks based on data analytics, and fostering collaborative partnerships through shared platforms. Policymakers should collaborate with industry stakeholders to develop regulatory frameworks that support digital transformation in supply chains. Clear guidelines and standards can promote adoption while ensuring data security, interoperability, and ethical use of emerging technologies like blockchain and big data analytics.